Randomized phase III and extension studies: efficacy and impacts on quality of life of naldemedine in subjects with opioid-induced constipation and cancer. (18th April 2018) - Katakami, N; Harada, T; Murata, T; Shinozaki, K; Tsutsumi, M; Yokota, T; Arai, M; Tada, Y; Narabayashi, M; Boku, N
Abstract: Background: The efficacy and safety of naldemedine (a peripherally acting µ-opioid receptor antagonist) for opioid-induced constipation (OIC) in subjects with cancer was demonstrated in the primary report of a phase III, double-blind study (COMPOSE-4) and its open-label extension (COMPOSE-5). The primary end point, the proportion of spontaneous bowel movement (SBM) responders, was met. Here, we report results from secondary end points, including quality of life (QOL) assessments from these studies. Patients and methods: In COMPOSE-4, eligible adults with OIC and cancer were randomly assigned 1:1 to receive once-daily oral naldemedine 0.2 mg ( n = 97) or placebo ( n = 96) for 2 weeks, and those who continued on to COMPOSE-5 received naldemedine for 12 weeks ( n = 131). Secondary assessments in COMPOSE-4 included the proportion of complete SBM (CSBM) responders, SBM or CSBM responders by week, and subjects with ≥1 SBM or CSBM within 24 h postinitial dose. Changes from baseline in the frequency of SBMs or CSBMs per week were assessed at weeks 1 and 2. Time to the first SBM or CSBM postinitial dose was also evaluated. In both studies, QOL impact was evaluated by Patient Assessment of Constipation-Symptoms (PAC-SYM) and PAC-QOL questionnaires. Results: Naldemedine improved bowel function for all secondary efficacy assessments versus placebo (all P ≤ 0.0002). The timely onset of naldemedine activity versus placebo was evidenced by median time to the first SBM (4.7 h versus 26.6 h) and CSBM (24.0 h versus 218.5 h) postinitial dose (all P < 0.0001). In COMPOSE-4, significant differences between groups were observed with the PAC-SYM stool domain ( P = 0.045) and PAC-QOL dissatisfaction domain ( P = 0.015). In COMPOSE-5, significant improvements from baseline were observed for overall and individual domain scores of PAC-SYM and PAC-QOL. Conclusions: Naldemedine provided effective and timely symptomatic relief from OIC and improved the QOL of subjects with OIC and cancer. Trial registration ID: www.ClinicalTrials.jp : JAPIC-CTI-132340 (COMPOSE-4) and JAPIC-CTI-132342 (COMPOSE-5).